Sparkes, Rev. North River. Photograph of people around a kitchen table and old woman blowing out candles on her birthday cake. - Sparkes, Rev. (1981)
Photo of Evelyn, Toss, John and to the right is sister fanny Pritchard This is Grandmother Florence Atkins Bradbury who is on the tape and is being interviewed by grandaughter Claudine Sparkes in 1982, Tom Heddersions Social Studies Class, Bishop O”Neville